2011
DOI: 10.1016/j.cub.2011.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DNA Replication through Sld3-Dpb11 Interaction Is Conserved from Yeast to Humans

Abstract: Cyclin-dependent kinases (CDKs) play crucial roles in promoting DNA replication and preventing rereplication in eukaryotic cells [1-4]. In budding yeast, CDKs promote DNA replication by phosphorylating two proteins, Sld2 and Sld3, which generates binding sites for pairs of BRCT repeats (breast cancer gene 1 [BRCA1] C terminal repeats) in the Dpb11 protein [5, 6]. The Sld3-Dpb11-Sld2 complex generated by CDK phosphorylation is required for the assembly and activation of the Cdc45-Mcm2-7-GINS (CMG) replicative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
180
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(190 citation statements)
references
References 30 publications
(47 reference statements)
5
180
0
Order By: Relevance
“…These observations raise additional questions about the order of assembly of additional pre-initiation factors at origins of DNA replication. In budding yeast the Rad4 TopBP1 homologue Dpb11 has been shown to interact with both Sld2 and Sld3 and those events have been shown to be CDK-dependent and similar data have recently been reported in metazoans (6,7,8,10,11,12,49). Chromatin association of Cdc45 has been previously shown to be dependent upon Mcm10, Rad4 TopBP1 , Sld3 and the GINS complex (22,23,24,47).…”
Section: ) Predictably Mcm4supporting
confidence: 61%
See 1 more Smart Citation
“…These observations raise additional questions about the order of assembly of additional pre-initiation factors at origins of DNA replication. In budding yeast the Rad4 TopBP1 homologue Dpb11 has been shown to interact with both Sld2 and Sld3 and those events have been shown to be CDK-dependent and similar data have recently been reported in metazoans (6,7,8,10,11,12,49). Chromatin association of Cdc45 has been previously shown to be dependent upon Mcm10, Rad4 TopBP1 , Sld3 and the GINS complex (22,23,24,47).…”
Section: ) Predictably Mcm4supporting
confidence: 61%
“…The phosphorylation-dependent Rad4 TopBP1 interaction with Sld2 and Sld3 is conserved between budding and fission yeast (48). Indeed the conservation of the TopBP1-Sld3 interaction has recently been extended to human cells (49). Taken together, we conclude from these data that Rad4 TopBP1 associates with origins of DNA replication where it is required for the assembly of the replication pre-initiation complex, specifically for the stable incorporation of Sld2, Sld3 and Mcm10.…”
Section: ) Predictably Mcm4supporting
confidence: 51%
“…The yeast homolog of Treslin, Sld3, is phosphorylated by Rad53 (the functional homolog of Chk1), and this phosphorylation has been shown to block late origin firing (31). Moreover, recent data have demonstrated that the interaction of Treslin with TopBP1 is inhibited upon replication fork stalling (22), and this abrogated interaction is Chk1-dependent. Thus, Treslin and TopBP1 may function not only upstream of ATR, being required for ATR-Chk1 pathway activation, but also downstream, as an ultimate effector of Chk1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…a Defined ATR Checkpoint System-Although an unbiased genetic screen identified Treslin as a novel replication/checkpoint regulator (11), and biochemical studies have discovered an interaction of Treslin with TopBP1 (15,22), the essential role of Treslin and TopBP1 in DNA replication initiation has prevented the analysis of Treslin function in checkpoint signaling. To further investigate this potential role, we decided to test Treslin in a defined in vitro ATR kinase assay developed in our laboratory.…”
Section: Chk1 Phosphorylation By Atr Is Stimulated By Treslin Inmentioning
confidence: 99%
See 1 more Smart Citation